Protection of wheat against leaf and stem rust and powdery mildew diseases by inhibition of polyamine metabolism - Weinstein, L H (Plant science : an international journal of experimental plant biology, 1987)
In higher plants, polyamines arise from arginine by one of two pathways: via ornithine and ornithine decarboxylase or via agmatine and arginine decarboxylase but in fungi, only the ornithine decarboxylase pathway is present. Since polyamines are required for normal growth of microorganisms and plants and since the ornithine pathway can be irreversibly blocked by alpha-difluoromethylornithine (DFMO) which has no effect on arginine decarboxylase, fungal infection of green plants might be controlled by the site-directed use of such a specific metabolic inhibitor. DFMO at relatively low concentrations provided effective control of the three biotrophic fungal pathogens studied, Puccinia recondita (leaf rust), P. graminis f. sp. tritici (stem rust), and Erysiphe graminis (powdery mildew) on wheat (Triticum aestivum L.) Effective control of infection by leaf or stem rust fungi was obtained with sprays of DFMO that ranged from about 0.01 to 0.20 mM in experiments where the inhibitor was applied after spore inoculation. The powdery mildew fungus was somewhat more tolerant of DFMO, but good control of the pathogen was obtained at less than 1.0 mM. In general, application of DFMO after spore inoculation was more effective than application before inoculation. Less control was obtained following treatment with alpha-difluoromethylarginine (DFMA) but the relatively high degree of control obtained raises the possibility of a DFMA to DFMO conversion by arginase